2018
DOI: 10.1002/ar.23808
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Innervation of the Bladder, External Urethral Sphincter and Clitoris: A Neuronal Tracing Study in Female Mongrel Hound Dogs

Abstract: Many studies examining the innervation of genitourinary structures focus on either afferent or efferent inputs, or on only one structure of the system. We aimed to clarify innervation of the bladder, external urethral sphincter (EUS) and clitoris. Retrograde dyes were injected into each end organ in female dogs. Spinal cord, mid-bladder, and spinal, caudal mesenteric, sympathetic trunk and pelvic plexus ganglia were examined for retrograde dye-labeled neurons. Neurons retrogradely labeled from the bladder were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 64 publications
(144 reference statements)
6
43
0
Order By: Relevance
“…Pelvic plexus‐induced bladder contractions significantly decreased by 1 year after decentralization that included the transection of all sacral roots, the dorsal roots of L7, and the hypogastric nerves, bilaterally, confirming a previous finding that the L7 dorsal root plays an important role in bladder sensation . Despite the significant decrease in the strength of bladder contraction, the preservation of smooth muscle function and at least some nerve activity may encourage successful surgical reinnervation after long‐term lower spinal root injury.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Pelvic plexus‐induced bladder contractions significantly decreased by 1 year after decentralization that included the transection of all sacral roots, the dorsal roots of L7, and the hypogastric nerves, bilaterally, confirming a previous finding that the L7 dorsal root plays an important role in bladder sensation . Despite the significant decrease in the strength of bladder contraction, the preservation of smooth muscle function and at least some nerve activity may encourage successful surgical reinnervation after long‐term lower spinal root injury.…”
Section: Discussionsupporting
confidence: 80%
“…The extensive decentralization in this study, which included transection of all sacral roots plus the dorsal root of L7, as well as the hypogastric nerves, bilaterally, was selected based on a previous study that identified the L7 dorsal root as one of the major sources of sensory neuron cell bodies innervating the bladder . Because these animals are part of a larger reinnervation study, we needed to ensure that the bladder was decentralized as much as possible to better evaluate the success of reinnervation.…”
Section: Discussionmentioning
confidence: 99%
“…; Pidsudko, ; Barbe et al. ). Therefore, differentiated chemical coding of the SPN may suggest that different populations of these perikarya supply discrete groups of CaMG neurons that project to specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…; Pidsudko, ; Barbe et al. ). The ganglia themselves are targeted by nerve fibres (NF) arising from different sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation